Buying Perfume in the Digital Age: A Study on E-Shoppers’ Perceptions and Typologies - Barbosa, Belem; Mahdavi, Mehdi; Oliveira, Zaila; Chkoniya, Valentina (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study aims to shed light on the factors that facilitate online purchase of perfume. It specifically: 1) explores the antecedents of online purchase behaviour in the case of experience goods; 2) analyses the motivations, perceived benefits and perceived risks associated with online purchase of perfume; and 3) identifies perfume e-shoppers’ profiles. Design/Methodology/Approach: A qualitative research approach involving interviewing 27 perfume e-shoppers from Brazil, Iran and Portugal was adopted. Research findings: The findings of this study reveal that there are three types of perfume e-shoppers: 1) experienced e-shoppers, 2) bargain e-seekers, and 3) expert e-shoppers. Competitive prices, enjoyable online experiences and greater varieties of perfumes are among the perceived benefits that motivate the online shoppers. The inability to test the perfumes, particularly those that are never tried before, appears to be the major drawback. Theoretical contribution/Originality: This study provides interesting cues on a topic that has so far been disregarded by the literature despite its growing importance as a business sector—online purchase of perfumes. It offers the categorisation of three e-shopper profiles, based on consumers’ narratives, and highlighted the importance of further addressing the dynamic nature of consumer behaviours, particularly in the online context. Practitioner/Policy implications: The findings show that the main trigger of buying perfume online is the price discounts, which is particularly important to less experienced Web shoppers. This indicates that experience goods such as perfume should, at the initial stage, be sold in stores that offer an assortment of products. Online perfume stores should consider alternatives to provide perfume testing. Research limitation/Implications: Purposive sampling does not allow results’ generalisation; hence future research is needed to further validate the findings. Keywords: E-shoppers’ Motivations, Experience Goods, Online Shopping, Perceived Benefits, Perceived Risks, Perfume JEL Classification: M10, M30, M31